2018
DOI: 10.1007/s00330-018-5621-x
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography for liver fibrosis in chronic hepatitis B: Adapting the cut-offs to alanine aminotransferase levels improves accuracy

Abstract: • The ALT-adapted dual cut-off values of LSMs showed high accuracy for diagnosis of the presence or absence of significant fibrosis and cirrhosis. • ALT levels did not influence the overall diagnostic accuracy for predicting significant fibrosis and cirrhosis. • The ALT-adapted dual cut-offs in patients with ALT levels > 2 × ULN were markedly higher than those in patients with ALT levels ≤ 2 × ULN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…With vibration-controlled transient elastography, the alanine aminotransferase-adapted cut-off values of liver stiffness reportedly improved the staging of liver fibrosis in patients with chronic hepatitis B in a single study (36). The consensus for the staging of liver fibrosis with vibration-controlled transient elastography, the consensus panel proposes a vendor-neutral "rule of four" (5, 9, 13, 17 kPa) for the ARFI techniques for viral etiologies and NAFLD: Liver stiffness of 5 kPa (1.3 m/sec) or less has high probability of being normal; liver stiffness less than 9 kPa (1.7 m/sec), in the absence of other known clinical signs, rules out cA-CLD; values between 9 kPa (1.7 m/sec) and 13 kPa (2.1 m/sec) are suggestive of cACLD but may need further test for confirmation; and values greater than 13 kPa (2.1 m/sec) are highly suggestive of cACLD.…”
Section: Recommendationsmentioning
confidence: 99%
“…With vibration-controlled transient elastography, the alanine aminotransferase-adapted cut-off values of liver stiffness reportedly improved the staging of liver fibrosis in patients with chronic hepatitis B in a single study (36). The consensus for the staging of liver fibrosis with vibration-controlled transient elastography, the consensus panel proposes a vendor-neutral "rule of four" (5, 9, 13, 17 kPa) for the ARFI techniques for viral etiologies and NAFLD: Liver stiffness of 5 kPa (1.3 m/sec) or less has high probability of being normal; liver stiffness less than 9 kPa (1.7 m/sec), in the absence of other known clinical signs, rules out cA-CLD; values between 9 kPa (1.7 m/sec) and 13 kPa (2.1 m/sec) are suggestive of cACLD but may need further test for confirmation; and values greater than 13 kPa (2.1 m/sec) are highly suggestive of cACLD.…”
Section: Recommendationsmentioning
confidence: 99%
“…In this study, the children were seriously ill, and their ALT and AST levels were significantly higher than normal, leading to an insignificant correlation with LSM. Zeng et al 28 reported that the LSM values were affected in patients with significantly higher ALT levels, but they had no effect in the normal group or in groups with slightly higher ALT levels.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the children were seriously ill, and their ALT and AST levels were significantly higher than normal, leading to an insignificant correlation with LSM. Zeng et al 28 reported that the LSM values were affected in patients with significantly higher ALT levels, but they had no effect in the normal group or in groups with slightly higher ALT levels. Edema, inflammation, extrahepatic cholestasis, and congestion can increase liver stiffness and elevate the measurements, 12,13,28 which are associated with higher LSM values on TE and ARFI, if this is true also for 2D‐SWE 29 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another common confounder is the presence of acute liver inflammation, which increases liver stiffness. Different liver stiffness thresholds adapted to normal and abnormally elevated liver transaminase levels for the detection of significant fibrosis and cirrhosis have been proposed and successfully implemented in studies involving patients with HBV, HCV, and alcoholic liver disease . Other biological confounders that increase liver stiffness without fibrosis include hepatic venous congestion, cholestasis, right heart failure, and infiltrative diseases such as amyloidosis.…”
Section: Ultrasoundmentioning
confidence: 99%